Application of TAM to Explore Awareness and Enjoyment of the Use of Artificial Intelligence ChatGPT in Students - Widji Dwi Rohana; Nugraha, Jaka; Inna Koblianska (Universitas Negeri Surabaya, 2025)
Phenomenon/Issue : The rapid development of artificial intelligence (AI) has influenced various aspects of human life, including education. ChatGPT, as a popular AI tool, is increasingly used by students in the learning process, yet its level of use and acceptance among students varies due to psychological factors and user perceptions. Purpose : To examine the influence of awareness and enjoyment on the acceptance of ChatGPT among first-year students using the Technology Acceptance Model (TAM) framework. Research Methods : A quantitative approach using a survey of 145 first-year students. Data were analyzed using Structural Equation Modeling (SEM) with the Generalized Structured Component Analysis (GSCA) method. Results : Awareness and enjoyment significantly affect perceived usefulness (PU) and perceived ease of use (PEOU). Perceived usefulness (PU) significantly influences behavioral intention to use (BITU), while perceived ease of use (PEOU) does not have a significant effect on behavioral intention to use (BITU). Research Contributions : The study expands the theoretical framework of the Technology Acceptance Model (TAM) by integrating the effects of awareness and enjoyment in explaining technology adoption, particularly in the context of ChatGPT use in education. The findings also provide insights for curriculum design and educational policy to enhance the benefits of AI technology in learning processes